EFEK PEMBERIAN TEH BUAH ZURIAT (Hyphaene Thebaica) TERHADAP MORFOMETRI OVARIUM MENCIT (Mus musculus) - Imanurdin, Megumi Nur Aninda; Zayani, Nofri (Nusantara Hasana Berdikari, 2022)
Abnormal the ovarian morphometry can result in poor quality oocytes produce so that it has a negative impact on the fetus being born. One of the factors that can interfere with ovarian morphometry is exposure to cigarette smoke. Interventions that can be given to overcome this problem is to provide high-antioxidant herbs, namely Zuriat fruit (Hyphaene thebaica L.). Objective: to determine the effect of zuriat fruit decoction on the ovarian morphometry of mice exposed to cigarette smoke. Methods: This study was a total experiment with a completely randomized design. Samples were taken using purposive sampling technique with a total of 12 mices. Mices were mated and exposed to kretek cigarette smoke for 5 days, followed by oral injection of zuriat fruit decoction for 10 days. Data on the length, width, and weight of the ovaries were collected on the 18th days of gestation. Data were analyzed by Analysis of variance (ANOVA) and Duncan Multiple New Range Test (DMNRT). Results: Treatment of decoction of zuriat fruit (Hypaeane thebaica) significantly affected the length, width, and weight of the ovaries of mice exposed to kretek cigarette smoke at Î±=1%. Conclusion: Decoction of zuriat fruit has a good effect on the ovarian morphometry of mices exposed to cigarette smoke as evidenced by an increase in the length, width, and weight of the ovaries at the best dose of 50 mg/kg.